EVALUATION OF THE INTELLECTUAL POTENTIAL OF A REGION IN THE CONTEXT OF INNOVATIVE DEVELOPMENT - O. V. Loseva; V. A. Dresvyannikov (Финансы: теория и практика)
The article discusses the innovative development of a region (based on available and newly created innovations) assuming a high quality intellectual potential. The intellectual potential of the region is understood as a set of two interrelated components — the resource potential that determines conditions and possibilities of the innovative activity and the achieved capacity representing the results of this activity. The structure of the region’s intellectual potential is shown. The principal elements of the methodology for its evaluation including the research basis, the semantic domain model, principles, objectives, functions, types, methods of assessment are described. Particular attention is paid to the development of non-financial evaluation methods based on statistical quality, use of a system of indicators, dynamics indices and ratings taking into account the entropy of partial indicators. The industrybased and statistical approaches to the assessment of the intellectual potential of the region are described.